1997
DOI: 10.4102/jsava.v68i2.873
|View full text |Cite
|
Sign up to set email alerts
|

Transient hyperammonaemia in an adult German shepherd dog : case report

Abstract: A 3-year-old male German shepherd dog was presented with severe generalised seizures. The dog was protein-intolerant and showed severe hyperammonaemia on ammonia stimulation. The hyperammonaemic state was present for at least 6 weeks and then spontaneously resolved. No obvious cause (liver disease, portocaval shunts, urea cycle enzyme deficiencies, drug therapy or urinary tract obstruction) could be identified. It is possible that this dog had a variation of transient hyperammonaemic syndrome, described in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Similar cases of hyperammonemia of unknown origin have also been described in humans and dogs. [12][13][14][15][16] Several similarities between the horse reported in this study and other equine patients were found with regard to history, clinical findings, and laboratory abnormalities. A postmortem examination was performed on 4 of the previously reported horses and showed similar findings.…”
mentioning
confidence: 63%
“…Similar cases of hyperammonemia of unknown origin have also been described in humans and dogs. [12][13][14][15][16] Several similarities between the horse reported in this study and other equine patients were found with regard to history, clinical findings, and laboratory abnormalities. A postmortem examination was performed on 4 of the previously reported horses and showed similar findings.…”
mentioning
confidence: 63%
“…Transient HA has been reported in Irish wolfhound pups and a similar syndrome has been observed in a mature German Shepherd dog (Meyer et al . 1996; Lobetti et al . 1997; Zandvliet and Rothuizen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Portosystemic shunts were considered unlikely, as survivors recovered completely and permanently and post mortem findings in nonsurvivors were not supportive of the diagnosis (Buonanno et al 1988;Fortier et al 1996). Transient HA has been reported in Irish wolfhound pups and a similar syndrome has been observed in a mature German Shepherd dog (Meyer et al 1996;Lobetti et al 1997;Zandvliet and Rothuizen 2007). Affected pups show no clinical signs and NH 4 + concentrations normalise at age 3-4 months and the authors suspected that a transient defect in NH4 + metabolism as the underlying cause (Zandvliet and Rothuizen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is thought to be due to a defective mitochondria1 ornithine transport protein, required in urea synthesis, resulting in hyperammonaemia and hyperornithinaemia. Transient hyperammonaemia has been described in a mature German Shepherd dog which presented with severe generalised seizures (Lobetti et al 1997). The dog was normoammonaemic during seizures, but developed severe hyperammonaemia when dosed with 100 mgkg bwt of ammonia.…”
Section: Discussionmentioning
confidence: 99%